Avaliação do risco de fratura osteoporótica por meio da ferramenta frax clínico em pacientes com doença pulmonar obstrutiva crônica - Xavier, Bruno Matheus Souza (2019)
Introduction: Osteoporosis is one of the main comorbidities of chronic obstructive pulmonary disease (COPD), due to the common risk factors. The World Health Organization (WHO) and the University of Sheffield, England have developed the Fracture Risk Assessment Tool (FRAX), which stratifies the absolute risk of osteoporotic fractures over the next 10 years. The aim of the study was to evaluate the absolute risk of osteoporotic fracture and indication of treatment for osteoporosis using the FRAX tool in COPD patients. Methods: This is a descriptive and cross sectional study with a quantitative approach and convenience sampling with 52 COPD patients at the Pulmonology Department of the University Hospital of the Federal University of Sergipe. The data collection instrument used was a structured questionnaire that addressed demographic data, risk factors for osteoporosis and osteoporotic fracture. Results: In this study, 42.3% of the participants should have been submitted to bone densitometry (DXA) only by the age factor as recommended by the WHO. When calculating the absolute risk of osteoporotic fracture by FRAX, it was observed that 19.3% in the control group and 42.3% in the group with COPD had absolute risk for hip fracture. When compared gender, women were more prone to fractures. Conclusion: COPD patients are at increased risk for osteoporotic fractures, especially hip fractures, when compared with people without the disease; In addition to the difficulty of performing DXA in our country, the use of the FRAX tool would help to intervene early, directing resources and treatment when necessary